MIGRATION OF THE POPULATION OF THE REPUBLIC OF ARMENIA IN 2019–2023 (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article analyzes and evaluates the state of interstate and intrastate migration flows in terms of settlement types and administrative units of the Republic of Armenia, the reasons for migration, the distribution of foreign immigrants, who received the temporary, permanent, and special residence statuses in Armenia by country of citizenship, as well as based on Armenian origin from 2019 to 2023. It examines the dynamics of net migration balance, border-crossing balance statistics of the republic, migration efficiency, migration tension, the migration intensity (mobility) coefficient, the gender and age composition of the population involved in interstate migrations, and changes in the population size of the marzes and the City of Yerevan in 2022–2023. The analysis of a wide range of absolute and relative indicators, cause-and-effect relationships of migration and the socio-demographic composition of the population, as well as the study of territorial differences in migration processes within the country, led to conclusions and recommendations for the development and implementation of migration policies and the targeted and effective management of immigration and emigration flows.
Keywords: migration of the population; net migration balance; migration tension; migration flows; Republic of Armenia